Formation of Cadets’ professional values by means of Professional English - Ляшенко, Уляна (Pedagogy of Higher and Secondary Education, 2014)
Lyashenko U. I. Formation of Cadets’ professional values by means of Professional English. The article is devoted to the problem of cadets’ professional values formation by means of Professional English at maritime educational establishments; the stages of cadets’ professional values formation are pointed out; the most suitable conditions for cadets’ professional values formation are defined; it is proved that implementation of cadets’ professional values at the Professional English lessons will be most effective.